2017
DOI: 10.1163/15691624-12341330
|View full text |Cite
|
Sign up to set email alerts
|

On the Benefit of a Phenomenological Revision of Problem Solving

Abstract: Problem solving has been empirical psychology’s concern for half a century. Cognitive science’s work on this field has been stimulated especially by the computational theory of mind. As a result, most experimental research originates from a mechanistic approach that disregards genuine experience. On the occasion of a review of problem solving’s foundation, a phenomenological description offers fruitful perspectives. Yet, the mechanistic paradigm is currently dominant throughout problem solving’s established pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Pseudo-interactivity is an experimental paradigm that encompasses behavioral studies, e.g., based on computer simulations. Its main purpose is the investigation of experiential differences between phenomenologically distinct types of situations, such as problems, challenges, and fatalities (see Wendt, 2017). Pseudo-interactivity allows for quantitative and qualitative measurements and it is not restrictive on the specific design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pseudo-interactivity is an experimental paradigm that encompasses behavioral studies, e.g., based on computer simulations. Its main purpose is the investigation of experiential differences between phenomenologically distinct types of situations, such as problems, challenges, and fatalities (see Wendt, 2017). Pseudo-interactivity allows for quantitative and qualitative measurements and it is not restrictive on the specific design.…”
Section: Methodsmentioning
confidence: 99%
“…In order to manifest these situational modes (Wendt, 2017) in the experimental design, the core element of pseudointeractive experimentation is semantic complexity instead of algorithmic complexity. While CPS experiments treat their parameters with a certain reluctance in order to cater to the common sense of the experimental subjects, pseudo-interactive experiments allow for extraordinary experimental behavior since it does not conservatively replicate the constraints of a plausible scenario.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its explanations are functionalist, such as the infamous idea of the problem as a relation between an initial and a goal state. Ultimately, problem finding, problem classification, problem space, and problem quality (Wendt, 2017a) are the most pertinent research topics. Upon examination of some recent psychological contributions to this tradition of problem-solving research, it can be shown nonetheless that fundamental concerns still have not been overcome and resolved, despite critical advances in the last decades.…”
Section: The Phenomenology Of the Problemmentioning
confidence: 99%
“…For psychology as an empirical discipline, which has sought to investigate problem-solving in the tradition of the classical “human problem solving” approach by Newell and Simon (1972), there does not seem to be an immediate conflict from the ambivalence either. Firstly, the theoretical construct of problem-solving can be determined by a functionalist formula, such as Newell’s and Simon’s idea of the “task environment”: problem-solving here refers to the transformation of an initial state into a goal state by overcoming barriers (for a detailed discussion of the cognitivist paradigm of problem-solving research, see Wendt, 2017a). Secondly, this operationalization is investigated on the basis of empirical data.…”
Section: Introductionmentioning
confidence: 99%